Prospects for the government of Pedro Sanchez in the context of socio-political situation in Spain - S. M. Khenkin (Ибероамериканские тетради)
The left and the right parties in modern Spain often approach many problems that the country faces very differently. In these conditions, the question of whether the left-wing coalition government led by Pedro Sánchez will remain in power until the end of 2023, when the next parliamentary elections are to take place, is of utmost importance. And if it does, will the Socialists win again, or will the initiative pass to the right forces? Government performance is assessed rather contradictory by the citizens of Spain and there are certain reasons for this. The country has embarked on the thorny path of overcoming the consequences of the pandemic. Many sectors of Spanish economy are recovering, the situation in the labour market has improved. But in general, the pace of economic recovery has not yet reached expected indicators and results. Inflation has risen because of rising electricity and gasoline prices, and the purchasing power of the population has declined. At the moment, the government’s prospects are largely determined by the relationship between the Spanish Socialist Workers’ Party and Unidas Podemos coalition. This relationship is very complex and contradictory, and as a result disagreements and conflicts arise quite often. An equally difficult question is whether the support of the separatist and nationalist parties of Catalonia and the Basque Country, without which the current government will lose its absolute majority in the lower house of parliament and cannot count on effective governance, will continue. The government’s choices are narrowed by the position of the right-wing parties that stand in stiff and uncompromising opposition and accuse it of complete irrelevancy. Tension reigns in public life with political situation remaining volatile and largely unpredictable.